Physiological traits, gene expression responses, and proteomics of rice varieties varying in heat stress tolerance at the flowering stage - Guo, Hui; Tao, Wei; Gao, Huiyong; Chen, Lei; Zhong, Xiaoyuan; Tang, Maoyan; Gao, Guoqing; Liang, Tianfeng; Zhang, Xiaoli (Frontiers in Plant Science, 2024)
Introduction/Background Global warming greatly limits the productivity of rice. Rice plants are highly sensitive to heat stress at the flowering stage. The selection of heat-tolerant varieties is considered the most effective approach for ensuring global food security in the coming decades. Methods Based on previous screening and QTL localization results, we selected tolerant varieties (Huang Huazhan, HZ) and susceptible varieties (Yang Dao6, YD) of rice and studied their physiological characteristics, gene expression responses, and proteomic differences of their anthers under heat stress. The differentially expressed proteins (DEPs) were validated by real-time PCR. Results The activities of the antioxidant enzymes CAT, SOD, POD, and APX were 8.36%, 9.56%, 20.61%, and 25.34% higher in HZ than in YD under heat stress, respectively. Similarly, the content of proline and soluble sugar was 8.32% and 14.47% higher in HZ than in YD, respectively. The content of MDA and H2O2 was 8.11% and 39.5% lower in HZ than in YD, respectively. The ratio of endogenous GA3/ABA in HZ was 10.65, which was significantly higher than that of YD (3.84). In addition, we validated the candidate genes LOC_Os08g07010 and LOC_Os08g07440 that our team located in 2021, and the result showed that the expression of these two heat-tolerant genes in the anthers was significantly higher in HH than in YH. DEPs involved in the response to heat stress were identified by TMT proteomics, five upregulated and three downregulated differential expression proteins in HH. DEPs were verified by RT-qPCR. Discussion These results provide new insights into the physiological characteristics, dominant DEPs, and gene expression responses in both rice varieties under heat stress. Our results indicate that the antioxidant and osmoregulatory capacities, the ratio of endogenous GA3 and ABA, these DEPs are mainly involved in the pathways of phenylpropanoid biosynthesis, ubiquitin-mediated proteolysis, carbohydrate metabolism, thiamine metabolism, protein processing in the endoplasmic reticulum, and folding, sorting, and degradation were upregulated to a greater degree in HZ than in YD. Additional studies were performed to clarify the roles of these proteins in response to heat stress.